Sustainable Transportation and Urban Form - Abbas, Sana Sati; Imran, Yahya Tayyeh (Iraqi Journal of Architecture and Planning, 2016)
The development of the means of transportation lead to travelling to new areas, and settled in suburban, so it was necessary to study the relationship between sustainable transportation and urban form .The research problem was that (there was a gab about the role of sustainable transportation in urban form). The aim of this paper is to build a theoretical frame work about this relationships. The paper described and analyzed two, Arabic and international samples, which have been chosen according to the variety of sustainable transportation as an urban strategy .The paper concluded that, the urban form based on sustainable transportation distinct, by cohesion and compactance at the local level, and multiplicity of nuclei in the large cities .The sustainable transport patterns by walking enhance the preservation of heritage and historical areas, also meets the human needs .